2011
DOI: 10.1021/jm1016279
|View full text |Cite
|
Sign up to set email alerts
|

Switching Reversibility to Irreversibility in Glycogen Synthase Kinase 3 Inhibitors: Clues for Specific Design of New Compounds

Abstract: Development of kinase-targeted therapies for central nervous system (CNS) diseases is a great challenge. Glycogen synthase kinase 3 (GSK-3) offers a great potential for severe CNS unmet diseases, being one of the inhibitors on clinical trials for different tauopathies. Following our hypothesis based on the enhanced reactivity of residue Cys199 in the binding site of GSK-3, we examine here the suitability of phenylhalomethylketones as irreversible inhibitors. Our data confirm that the halomethylketone unit is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 64 publications
4
71
0
2
Order By: Relevance
“…For example, we have a long standing interest in accessing [ 18 F]4-fluorophenacylbromide ([ 18 F]FPB, 3 ) via [ 18 F]FAP ( 2 ), due to its potential as a PET radiotracer for glycogen synthase kinase-3 (GSK-3) 40 . Typical yields of [ 18 F]FAP synthesized via traditional S N Ar chemistry (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…For example, we have a long standing interest in accessing [ 18 F]4-fluorophenacylbromide ([ 18 F]FPB, 3 ) via [ 18 F]FAP ( 2 ), due to its potential as a PET radiotracer for glycogen synthase kinase-3 (GSK-3) 40 . Typical yields of [ 18 F]FAP synthesized via traditional S N Ar chemistry (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Manzamine A specifically inhibits GSK-3β and CDK5 (the two key players in the hyperphosphorylation of tau protein in AD) with IC 50 s of 10 and 1.5 μM respectively; it is ineffective toward others kinases tested (Hamann et al, 2007). Kinetic studies indicated an ATP non-competitive inhibition regarding GSK-3 (Hamann et al, 2007) while susbstrate competitive inhibition has been recently proved experimentally (Palomo et al, 2011). …”
Section: Organic Molecules As Gsk-3 Inhibitorsmentioning
confidence: 99%
“…In this case, inactivation of the enzyme is due to the formation of an irreversible covalent sulfur–carbon bond between the key cysteine 199 located at the entrance to the ATP site of GSK-3 and the HMK moiety (Perez et al, 2011). …”
Section: Organic Molecules As Gsk-3 Inhibitorsmentioning
confidence: 99%
“…Compounds 14 and 15 are reversible GSK-3 inhibitors in the low micromolar or high nanomolar range and can be used as chemical precursors for the corresponding halomethylketones (HMKs). These HMKs are irreversible inhibitors, they alkylate Cys199, which is located in the ATP binding site of GSK-3 [41]. Further maleimide derivatives are listed in Table 3.…”
Section: Small-molecule Inhibitors Of Glycogen Synthase Kinasementioning
confidence: 99%